Cell membrane disintegration and extracellular vesicle release in a model of different size and charge PAMAM dendrimers effects on cultured endothelial cells. Issue 5 (28th May 2019) - Patel, Mehulkumar; De Paoli, Silvia H.; Elhelu, Oumsalama K.; Farooq, Sehrish; Simak, Jan
Abstract: Different nanomaterials are under development for various biomedical applications in which nanoparticles contact blood and vasculature. Therefore, investigating the interactions between nanomaterials and vascular endothelial cells (ECs) is of great importance. Here, we show the effects of polyamidoamine (PAMAM) dendrimers of two different sizes, generation 2 (G2; approximately 3  nm diameter) and generation 7 (G7; 9  nm), with neutral (OH-terminated), anionic (COOH-terminated), and cationic (NH2 -terminated) surface modifications on cultured human umbilical vein ECs (HUVECs). We found that only cationic dendrimers (5–100  μg/mL G7-NH2 and 100  µg/mL G2-NH2 ) and not anionic or neutral dendrimers were cytotoxic to HUVECs. In addition, cationic dendrimers at low concentrations (5  μg/mL) markedly increased the HUVEC surface expression of the proinflammatory activation marker ICAM-1 and phosphatidylserine (PS). Both G2-NH2 and G7-NH2 dendrimers caused g 1 arrest, but only G7-NH2 dendrimers induced significant HUVEC apoptosis. G7-NH2 interacted strongly with HUVEC plasma membranes and mitochondrial membranes, and phospholipid vesicles containing G7-NH2 formed, which resulted in extensive plasma membrane blebbing and disintegration. Furthermore, flow cytometric analysis showed that G7-NH2 -treated HUVECs released large numbers of extracellular vesicles (EVs) positive for CD105 and PS. A notable population of EVs positive for the mitochondrial marker TOM20 but negative for the autophagosome marker LC3 was found. In summary, large cationic PAMAM dendrimers (G7-NH2 ) showed both proinflammatory and proapoptotic effects in ECs; at high dendrimer concentrations, these effects were accompanied by necrotic cytotoxicity. G7-NH2 caused plasma and mitochondrial membrane disintegration and the release of EVs, including EVs of mitochondrial origin that were not associated with mitophagy.